(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The purpose of this paper is to determine and describe the library culture in Croatian public libraries. Semi-structured interviews with 14 library directors (ten public and four academic) were conducted. The tentative discussion topics were: definition of quality, responsibility for quality, satisfaction with library services, familiarization with user perspective of library and librarians, monitoring of user expectations and opinions. These interviews incorporate some of the findings of the project Evaluation of library and information services: public and academic libraries. The project investigates library culture in Croatian public and academic libraries and their preparedness for activities of performance measurement. The interviews reveal that library culture has changed positively in the past few years and that library leaders have positive attitude towards quality and evaluation activities. Library culture in Croatian libraries is a relatively new concept and as such was not actively developed and/or created. This article looks into the library culture of Croatian libraries, but at the same time investigates whether there is any trace of culture of assessment in them. Also, this article brings the latest update on views, opinions and atmosphere in Croatian public and academic libraries.